A fractionally loaded boundary value problem two-dimensional in the spatial variable - Kosmakova, M.T.; Izhanova, K.A.; Kasymova, L.Zh. (Bulletin of the Karaganda University. Mathematics series, 2023)
In the paper, the boundary value problem for the loaded heat equation is solved, and the loaded term is represented as the Riemann-Liouville derivative with respect to the time variable. The domain of the unknown function is the cone. The order of the derivative in the loaded term is less than 1, and the load moves along the lateral surface of the cone, that is in the domain of the desired function. The boundary value problem is studied in the case of the isotropy property in an angular coordinate (case of axial symmetry). The problem is reduced to the Volterra integral equation, which is solved by the method of the Laplace integral transformation. It is also shown by direct verification that the resulting function satisfies the boundary value problem.
Keywords: loaded boundary value problem; heat equation; isotropy; Volterra integral equation; Laplace transformation